An Audit of Emergency Department Accreditation Based on Joint Commission International Standards (JCI) - Hashemi, Behrooz; Motamedi, Maryam; Etemad, Mania; Rahmati, Farhad; Forouzanfar, Mohammad Mehdi; Kaghazchi, Fatemeh (Archives of Academic Emergency Medicine, 2014)
Introduction: Despite thousands of years from creation of medical knowledge, it not much passes from founding the health care systems. Accreditation is an effective mechanism for performance evaluation, quality enhancement, and the safety of health care systems. This study was conducted to assess the results of emergency department (ED) accreditation in Shohadaye Tajrish Hospital, Tehran, Iran, 2013 in terms of domesticated standards of joint commission international (JCI) standards. Methods: This is a cohort study with a four months follow up which was conducted in the ED of Shohadaye Tajrish hospital in December 2013. The standard evaluation check list of Iran hospitals (based on JCI standards) included 24 heading and 337 subheading was used for this purpose. The effective possible causes of weak spots were found and their solutions considered. After correction, assessment of accreditation were repeated again. Finally, the achieved results of two periods were analyzed using SPSS version 20. Results: Quality improvement, admission in department and patient assessment, competency and capability test for staffs, collection and analysis of data, training of patients, and facilities had the score of below 50%. The mean of total score for accreditation in ED in the first period was 60.4±30.15 percent and in the second period 68.9±22.9 (p=0.005). Strategic plans, head of department, head nurse, resident physician, responsible nurse for the shift, and personnel file achieved the score of 100%. Of total headings below 50% in the first period just in two cases, collection and analysis of data with growth of 40% as well as competency and capability test for staffs with growth of 17%, were reached to more than 50%. Conclusion: Based on findings of the present study, the ED of Shohadaye Tajrish hospital reached the score of below 50% in six heading of quality improvement, admission in department and patient assessment, competency and capability test for staffs, collection and analysis of data, training of patients, and facilities. While, the given score in strategic plans, head of department, head nurse, resident physician, responsible nurse for the shifts, and personnel file was 100%.